2022
DOI: 10.1021/acs.biomac.2c00053
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Hydrogels of Stimuli-Responsive Elastin and Calmodulin-Based Triblock Copolypeptides for Controlled Drug Release

Abstract: A variety of block copolypeptides with stimuli responsiveness have been of growing interest for dynamic self-assembly. Here, multistimuli-responsive triblock copolypeptides composed of thermosensitive elastin-based polypeptides (EBP) and ligand-responsive calmodulin (CalM) were genetically engineered, over-expressed, and nonchromatographically purified by inverse transition cycling. Diluted EBP-CalM-EBP (ECE) triblock copolypeptides under physiological conditions self-assembled into vesicles at the nanoscale b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Depending on the conformational change of the CalM middle block brought about by binding either Ca 2+ or Ca 2+ and trifluoperazines (TFPs) as ligands, they displayed controlled rheological and mechanical properties. 65 Turabee et al aimed at delivering protein molecules without deteriorating their inherent bioactivity through fabrication of a temperature- and pH-responsive bioresorbable injectable hydrogel system composed of polypeptide block copolymers, namely polyethylene glycol (PEG), temperature-responsive poly(γ-benzyl- l -glutamate) (PBLG), and pH-responsive oligo(sulfamethazine) (OSM), for the sustained delivery of proteins in vivo . The anionic properties of the scaffold allowed for the efficient loading of the model protein-lysozyme and when injected into the Sprague-Dawley rats subcutaneously, it was observed that the lysozyme loaded block copolymer formed a viscoelastic gel in vivo which could deliver the model protein in a sustained manner for at least a week.…”
Section: Neoteric Breakthroughs Of Organo-hydrogels Having Biomedical...mentioning
confidence: 99%
“…Depending on the conformational change of the CalM middle block brought about by binding either Ca 2+ or Ca 2+ and trifluoperazines (TFPs) as ligands, they displayed controlled rheological and mechanical properties. 65 Turabee et al aimed at delivering protein molecules without deteriorating their inherent bioactivity through fabrication of a temperature- and pH-responsive bioresorbable injectable hydrogel system composed of polypeptide block copolymers, namely polyethylene glycol (PEG), temperature-responsive poly(γ-benzyl- l -glutamate) (PBLG), and pH-responsive oligo(sulfamethazine) (OSM), for the sustained delivery of proteins in vivo . The anionic properties of the scaffold allowed for the efficient loading of the model protein-lysozyme and when injected into the Sprague-Dawley rats subcutaneously, it was observed that the lysozyme loaded block copolymer formed a viscoelastic gel in vivo which could deliver the model protein in a sustained manner for at least a week.…”
Section: Neoteric Breakthroughs Of Organo-hydrogels Having Biomedical...mentioning
confidence: 99%
“…37,38 We conclude that intramolecular α-helices are the driving force for gelation in PZLY-PEG PPU hydrogels via self-assembly of lysine segments, which has been observed in amphiphilic polylysine copolymer systems. 39–41 Simultaneously, cooperative intramolecular bonding of α-helical domains can provide significant mechanical reinforcement, which has been shown to dictate properties, such as moduli and recovery of hybrid networks. 27,42,43…”
Section: Resultsmentioning
confidence: 99%
“…The modified pET-21a (+) (mpET-21a) vector with an adaptor DNA sequence was prepared, as previously reported. , The adaptor of mpET-21a has the identical cleavage site of BseRI and AcuI and leaves two different sticky ends of XbaI and BamHI for seamless ligation of EBP n and anti-Flt1-EBP n encoded genes. EBP n with the pentapeptide unit of Val-Pro-Ala-X aa -Gly (VPAXG), where X at the fourth residue is an amino acid except Pro, is composed of n integer repeats of the six pentapeptides with the X composition of Ala:Gly:Ile of 1:4:1.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…They were screened to determine a length of EBP1 gene by agarose gel electrophoresis with double digestion of XbaI and BamHI and confirmed by DNA sequencing. When a series of genes of EBP n ( n = 1–6) were constructed, EBP12 and EBP24 were prepared by serial multimerization of EBP6 gene by modified recursive directional ligation (RDL), as reported. ,, Likewise, to construct various genes encoding anti-Flt1-EBP n ( n = 3, 6, 12, 24), 90 pmol annealed anti-Flt1 peptide-encoded dsDNA with both BseRI and AcuI cohesive ends was incubated with 30 pmol BseRI-restricted EBP n -encoding mpET-21a vector using 1 U T4 DNA ligase for ligation. Both gene and its length of anti-Flt1 peptide and EBP n were confirmed with XbaI and BamHI digestion by agarose gel electrophoresis and DNA sequencing.…”
Section: Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation